Sidang Ilahi Elohim Dalam Mazmur 82:1 - Marthin Steven Lumingkewas; Firman Panjaitan (Sekolah Tinggi Teologi Sriwijaya, 2020)
In the Old Testament Yahweh is frequently called El. The question is raised whether Yahweh was a form of the god El from the beginning or whether they were separate deities who only became equated later. They whom uphold theory Yahweh and El were conceived as separate deities holds that Yahweh was a southern storm god from Seir and so on, which was brought by the Israelites and conflated with the Jerusalem patriarchal deity.On the other side there are scholars who hold and conceived Yahweh and El as one single deity. These scholars defend this position most commonly on the grounds that no distinction between the two can be clearly found in the Hebrew Bible. The methodology used in this paper is literary – historical and social interpretations, with the main method being the